Technology practice among Independent Malay and Indian oil palm smallholders in Ramp 1, mukim of Hutan Melintang, Perak - Mutukumaran Subramanian (Tanjong Malim, 2014)
Technology practice among Independent Malay and Indian oil palm smallholders in Ramp 1, mukim of Hutan Melintang, Perak by Mutukumaran Subramanian